ANALISIS MODIFIKASI LEADING EDGE HULL VANE TIPE NACA 4412 TERHADAP SEAKEEPING KAPAL MENGGUNAKAN METODE CFD - Muhammad Luthfi (2023)
Seakeeping is the ability of a ship to stay above the waves. The ship's seakeeping ability is influenced by factors outside the ship. The use of a hull vane on a ship can reduce the up and down motion of the ship, namely pitching which is one of the six degrees of freedom. The hull vane uses a modified NACA 4412 with an amplitude of 2 mm and a 30 mm wave with angle of attack variations of 30, and 70 at a speed of Fn 0.4 and with regular waves, with a placement position of 40 mm trailing edge draft and 85 mm trailing edge AP, and using the destroyer hull model DTMB 5415. The analysis was conducted using the Computational Fluids Dynamics (CFD) method using Ansys Aqwa software. Based on the simulation results, NACA 4412 with modification and angle of attack 70 has the lowest pitch value among other variations.